Soybean mosaic disease (SMD): a review. Issue 1 (1st January 2021) - Rehman, Fazal Ur; Kalsoom, Maria; Adnan, Muhammad; Naz, Nageen; Ahmad Nasir, Tuffail; Ali, Husnain; Shafique, Talha; Murtaza, Ghulam; Anwar, Samra; Arshad, Muhammad Awais
ABSTRACT: Soybean Mosaic Disease (SMD) is one of the most serious, devastating, and widespread diseases of Glycine max (L.) Merry. caused by Soybean Mosaic Virus (SMV). It is more prevalent in low-lying and warm areas of soybean cultivation. SMV is also associated with severe mosaic, epinasty, and premature death of Passiflora spp. By soybean ( Glycine max ) seed, the transmission of soybean mosaic virus is at very rear chances. The studies and investigations made in the field of resolving the issues of transmission of soybean mosaic virus suggest that infected seed plays a vital role in disease transmission, but still there are no proper investigations to study the roles of several factors that may influence the SMV seed transmission. These are virus classification, virus transmission and establishment, symptoms of damage, electron microscopy, viral morphology, and control, which have been reviewed in this review article from currently available sources.